Pengaruh Penggunaan Tiktok Live terhadap Sikap Percaya Diri Mahasiswa Universitas Islam Riau - Ivan Taufiq; Beva Rahmadani (Syntax Literate, 2023)
This study aims to determine the effect of using TikTok live on the confident attitude of Universitas Islam Riau students and to find out the factors that influence it. The methods used in this study are quantitative surveys, data collection using questionnaires, interviews, documentation, and observation. To determine the effect of using TikTok live on the confident attitude of Universitas Islam Riau students, the author uses a simple linear regression analysis. Variable X in this study is the use of TikTok live, while variable Y is the confident attitude of Riau Islamic University students. The number of samples in the study was 65 people, the sampling technique was stratified sampling. Data processing The questionnaire trial was conducted using the Windows Product and Service Solution (SPSS) Statistical Program version 19.0. The results of this study show the influence of using TikTok live on the confident attitude of Universitas Islam Riau students. This is based on data analysis using simple linear regression is Y = 19.30 + 0.29 X with t count 2.069 greater than t table 1.998 and significance level 0.043 smaller compared to Î±, obtained from N = 65 and Î± = 0.05. Therefore, Ho was rejected and Ha was accepted because there was a significant influence between the use of tiktok live on the confident attitude of Universitas Islam Riau students, as for the factors that influence accessing tiktok live, namely technology is very easy to reach, ease of accessing the internet, and environmental factors due to support from parents and friends of respondents